Another look at the role of priests and rabbis after the destruction of the Second Temple - Lier, Gudrun (Journal for semitics, 2007)
In some recent targumic studies it was contended that a priest-centred society continued to control the synagogues in Post-Temple Judaism, while rabbis saw their main institution as the beth midrash. The distinction between the roles of rabbis and priests after the destruction is contrary to the standard scholarly picture. The new theory has direct implications for the question of contextualisation of Pentateuchal targums. The paper re-investigates the roles played by priests and rabbis in the age of formative Judaism in Palestine in the contexts of the beth knesset, beth midrash and beth din. It looks at the functions of Judaism's main institutions in the post-destruction era, asking who the teachers / leaders of the Post-Temple synagogues and academies were and what happened to the priesthood in the wake of the destruction. The evolvement of the title of "rabbi" also comes into the discussion.